L’oeil de la montagne : sur la recherche photographique de Marik Boudreau - Lamarre, André (CV Photo)

(untitled) (Les Productions Ciel variable, 2003)
Abstract With Miradors, which bears the subtitle Essai photographique sur l’érosion (Photographic essay on erosion), Marik Boudreau has produced a synthesis of her work on abandoned sites and urban ruins. An attentive reading of the key words given by the artist shows the rigour and complexity of her project. Between the mountains of Andalusia and the cities of Brazil, she opposes points of view from on high to those gazing up from below, the nudity of stone and the urban accumulation. She is interested in the fundamental processes of erosion and stratification. Her commentary is philosophical, aesthetic, and political.